Kompetensi Dosen Menurut Mahasiswa Psikologi Universitas Brawijaya - Yulianik, Endah (Persona:Jurnal Psikologi Indonesia, 2018)
The purposeÂ of this research is to know the competence of lecturer according to students Of Psychology University of Brawijaya. This research uses qualitative survey method with explorative type. Sampling method using non-probability sampling with a purposive sampling technique. The sample in this research is the student of psychology, University of Brawijaya generation 2014 totaling 107 students. Analytical techniques used are thematic analysis technique Boyatzis by using the Microsoft Excel program and R-Studio Package RQDA.Based on the results of the research competence of lecturer according to students of psychology. it can be concluded that the competence of the lecturers most needed by students in a row is the competence of personality 42.25%, the competence of social 24.95%, the competence of pedagogic 23.07% and the competence of professional 9.08%, which is shown based on the percentage of the highest to the lowest.Keywords: The competence of lecturers, Students of psychology